Unravelling the mysteries of underdevelopment in Africa - Elvis Dze Achuo; Tii Njivukuh Nchofoung; Simplice Asongu; Gildas Dohba Dinga (African Governance and Development Institute (AGDI), 2021)
Achieving sustainable development has been the dream of every society across the globe especially sequel to the dawn of the industrial revolution. Thus, understanding the fundamental determinants of the socio-politico-economic development of every economy is of prime importance for investors, policymakers, development agencies and the society at large. It is in this light that this study sought to empirically examine the key factors that explain the socioeconomic development patterns in Africa. The Instrumental Variable Two Stage Least Squares (IV-2SLS) estimation technique is adopted for a panel of 38 African countries over the 1996-2019 period. The empirical findings reveal that financial development and human capital are development enhancing in Africa while external financial inflows are detrimental to economic development. In addition, when other specific macroeconomic and structural variables were introduced in the model, the results show that institutional quality through governance, natural resources abundance, and industrialisation all explain both the social and economic development dynamics. These results were specific to income group, export structures and level of development. Moreover, salient policy implications are discussed.
Keywords: 330; Underdevelopment; Financial development; Human capital; Institutional quality; Africa